Implementation stages to the formation of a digital profile for participants in the educational process - Zavolodko, Ganna; Trubchaninova, Karina (International Education Development Center, 2025)
In the context of education digitalization, the concept of a digital profile is becoming increasingly vital as a component of digital literacy, personal development, and academic integrity. This article proposes a comprehensive methodological approach to the formation of digital profiles for students and educators. The digital profile is defined as a structured set of data reflecting an individual’s identity, activities, achievements, and interactions in digital environments. The paper outlines a four-stage model that includes initial digital hygiene, conscious identity building, academic integration, and long-term professional development. This methodological framework aims to promote the use of digital tools for personalized learning, strategic career planning, and responsible participation in the information society. It highlights the importance of forming digital culture and ethics from an early age and underlines the digital profile as a long-term reputational asset. The proposed approach supports sustainable digital development and provides a foundation for future educational and policy initiatives in digital literacy.
Keywords: digital profile; digital identity; digital literacy; digital culture; education; personalized learning; digital reputation; learning analytics; academic integrity; sustainable development